Liquid chromatography–tandem mass spectrometry assay for the simultaneous determination of apalutamide and its active metabolite N-desmethyl apalutamide, and its application in real-world patients with castration-resistant prostate cancer - Zhu, Yuxuan; Chen, Lu; Cheng, Wenqiang; Yang, Dingyuan; Zhang, Lijuan; Li, Jun (Frontiers in Pharmacology, 2025)
BackgroundApalutamide is used in the treatment of castration-resistant prostate cancer. A simple, specific, selective, and effective liquid chromatography–tandem mass spectrometry method for quantifying apalutamide and its active metabolite concentration in human plasma was developed and validated according to the FDA and EMA validation guidelines.MethodsA total of 24 patients diagnosed with desmoplasia-resistant prostate cancer (NM-CRPC) were recruited. Blood samples were drawn after 4 weeks’ administration of apalutamide at a dose of 180 mg once daily to ensure steady-state blood levels were achieved. Apalutamide and N-desmethyl apalutamide were analysed by quantitative liquid chromatography tandem mass spectrometry to measure the concentrations among individuals and the effect on the baseline level of prostate-specific antigen (PSA) and adverse events.ResultsThe linear range, precision, accuracy, matrix effect, recovery, carryover, and stability were appropriate according to the FDA and EMA validation guidelines. The apalutamide blood concentration range of the 24 patients was 0.517–7.27 μg/mL, and the median value was 4.92 μg/mL. The N-desmethyl apalutamide blood concentration range was 1.78–8.32 μg/mL, and the median value was 5.71 μg/mL. The median serum PSA level decreased from 61.03 (range 0.57–885.93) ng/mL at baseline to 0.970 (range 0.01–47.9) ng/mL at week 4.ConclusionTherapeutic drug monitoring can help evaluate the individual differences between patients taking apalutamide. A dose of 180 mg could reduce the baseline PSA level significantly (p < 0.05), and the incidence of skin rash was less compared to that of a dose of 240 mg.